Anatomical variability of the soleus muscle: A key factor for the prognosis of injuries? - Pedret, C.; Rupérez, F.; Mechó, S.; Balius, R.; Rodas, G. (Sports Medicine, 2022)
Calf muscles are among the most commonly injured muscles in athletes [1] (especially in amateurs). To precisely predict the prognosis of the injuries and the time of return to play (RTP), the anatomical location of calf muscles and the involvement of connective tissue have been studied through different imaging techniques.